Adaptive multimedia retrieval. Context, exploration, and fusion 8th International Workshop, AMR 2010, Linz, Austria, August 17-18, 2010, Revised Selected Papers - Detyniecki, Marcin; Knees, Peter; Nürnberger, Andreas; Schedl, Markus; Stober, Sebastia (Lecture Notes in Computer Science, 2011)
This book constitutes the refereed proceedings of the 8th International Conference on Adaptive Multimedia Retrieval, AMR 2010, held in Linz, Austria, in August 2010. The 14 revised full papers and the invited contribution presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on Context-based personalization; media information fusion; video retrieval; audio and music retrieval; adaptive similarities; and finding and organizing.